Multiple directorships, diligence and firm performance : an empirical analysis of Malaysian public listed company - Siti Balqis binti Mohd Noor (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
Multiple directorships are found to be common among outside directors (KPMG, 2009). The fact that these directors are busy and may lack the time to carry out their duties effectively and efficiently initiated the issuance of a requirement under the Bursa Malaysia Listing Requirements to limit the number of directorships held by an individual director to five (BM, 2012). Previous literature however, does not show robust findings concerning the ineffectiveness of these directors in performing their role. Using samples of Main Market Bursa Malaysia firms, this study aims to examine the impact of multiple directorships and diligence on firm performance and investigate the presence of moderating effect of diligence especially in the context of Malaysia. Multiple directorships are measured by the number of outside directorships held by independent directors and diligence is measured by the number of board meeting attendance of independent directors. Two theories are employed in this study which is agency theory and resource dependence theory. The results revealed that a higher number of multiple directorships results in higher firm performance, and no significant relationship is found between diligence and firm performance. Besides, the results also showed that the attendance at board meetings of independent directors with multiple directorships does not add value to firms.